High-Resolution Crustal S-wave Velocity Model and Moho Geometry Beneath the Southeastern Alps: New Insights From the SWATH-D Experiment - Sadeghi-Bagherabadi, Amir; Vuan, Alessandro; Aoudia, Abdelkrim; Parolai, Stefano; , The AlpArray and AlpArray-Swath-D Working Group; Heit, B.; Weber, M.; Haberland, C.; Tilmann, F. (Frontiers in Earth Science, 2021)
We compiled a dataset of continuous recordings from the temporary and permanent seismic networks to compute the high-resolution 3D S-wave velocity model of the Southeastern Alps, the western part of the external Dinarides, and the Friuli and Venetian plains through ambient noise tomography. Part of the dataset is recorded by the SWATH-D temporary network and permanent networks in Italy, Austria, Slovenia and Croatia between October 2017 and July 2018. We computed 4050 vertical component cross-correlations to obtain the empirical Rayleigh wave Green's functions. The dataset is complemented by adopting 1804 high-quality correlograms from other studies. The fast-marching method for 2D surface wave tomography is applied to the phase velocity dispersion curves in the 2-30 s period band. The resulting local dispersion curves are inverted for 1D S-wave velocity profiles using the non-perturbational and perturbational inversion methods. We assembled the 1D S-wave velocity profiles into a pseudo-3D S-wave velocity model from the surface down to 60 km depth. A range of iso-velocities, representing the crystalline basement depth and the crustal thickness, are determined. We found the average depth over the 2.8-3.0 km/s and 4.1-4.3 km/s iso-velocity ranges to be reasonable representations of the crystalline basement and Moho depths. The basement depth map shows that the shallower crystalline basement beneath the Schio-Vicenza fault highlights the boundary between the deeper Venetian and Friuli plains to the east and the Po-plain to the west. The estimated Moho depth map displays a thickened crust along the boundary between the Friuli plain and the external Dinarides. It also reveals a N-S narrow corridor of crustal thinning, to the east of the junction of Giudicarie and Periadriatic lines, which was not reported by other seismic imaging studies. This corridor of shallower Moho is located beneath the surface outcrop of the Permian magmatic rocks and seems to be connected to the continuation of the Permian magmatism to the deep-seated crust. We compared the shallow crustal velocities and the hypocentral location of the earthquakes in the Southern foothills of the Alps. It revealed that the seismicity mainly occurs in the velocity band between ~3.1 and ~3.6 km/s.